Innovative Formulation of a Facial Serum Using Avocado Oil (Persea americana Mill.) as a Facial Skin Moisturizer - Rahmat Muliadi; Astrid Indalifiany; Fery Indradewi Armadany; Vica Aspadiah; Wa Ode Nur Alidah (Journal of Pharmaceutical and Natural Resources, 2026)
Ultraviolet radiation, temperature, and humidity can cause a reduction in the skin's moisture content, leading to dryness. Therefore, an effective moisturizing preparation is required to maintain skin hydration. Avocado (Persea americana Mill.) oil is known to contain unsaturated fatty acids, vitamins, and antioxidants, making it a potential natural moisturizer. This study aimed to formulate a facial serum utilizing avocado oil as the active ingredient and to evaluate its physical characteristics, stability, and moisturizing activity. An experimental approach was employed, creating four facial serum formulations with avocado oil concentrations of 0%, 5%, 10%, and 15%. The evaluations encompassed organoleptic properties, homogeneity, pH, adhesiveness, spreadability, viscosity, phase separation, and emulsion type. Physical stability was assessed using the cycling test method, and moisturizing activity was evaluated in vitro. The results indicated that all formulations exhibited good physical characteristics, were homogeneous, experienced no phase separation, were oil-in-water (O/W) emulsions, and possessed pH values compatible with the skin's physiological pH. The preparations maintained physical stability following the cycling test. Furthermore, the moisturizing activity tests revealed that an increased concentration of avocado oil enhanced the moisturizing efficacy, with formula F3 (15%) yielding the highest moisture values: 52.830% before the cycling test and 42.970% afterward. Based on these findings, it can be concluded that the avocado oil-based facial serum, particularly formula F3, demonstrates the potential to be developed as a stable, safe, and effective facial skin moisturizer